ANALISIS REMBESAN TERHADAP KEAMANAN BENDUNGAN KEDUNG OMBO DI GROBOGAN, JAWA TENGAH - Rais Buldan; Suharyanto Suharyanto; Najib Najib; Kresno Wikan Sadono (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2021)
A dam, besides having a great benefits to meet human needs, it also can be a big disaster in addition to the dam collapsing. One of the main causes of failure of an embankment dam is the occurrence of excessive seepage which triggers piping events that can disturb the stability and safety of the dam. In general, the body of the Kedung Ombo Dam is in good condition, but there are several problems, such as the drain holes that are overgrown with dense grass which indicates that seepage has occurred. Therefore, it is necessary to evaluate the seepage to determine the safety level of the Kedung Ombo Dam. This study aims to analyze the condition of pore water pressure and seepage that occurs in the body of the Kedung Ombo Dam and to determine the level of safety of the dam body. The analyze was carried out using seepage monitoring instruments installed on the dam, namely the Piezometer and V-Notch at the Kedung Ombo Dam in 2021. Based on the results of the analysis, it was found that the pore water pressure and seepage discharge that occurred in the Kedung Ombo Dam were generally still within the permissible limits. According to the analysis results of the seepage index, the highest QI value is 0.09 at the maximum flood water level of +95 m, where the safety criteria for the seepage index is QI <1. Therefore it indicates that the seepage condition index at the Kedung Ombo Dam are still in a safe condition.Keywords: pore water pressure, seepage, piezometer, V-Notch, seepage index